Evaluasi Penerapan Kebijakan Batasan Bruto Pada Wajib Pajak OP UMKM - Simarmata, Reinhard Sahat Maruli; Yulianti, Yulianti (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p16, 2024)
This study aims to evaluate the policy of final income tax exemption for individual SME taxpayers with a turnover of up to Rp 500 million, in accordance with the Tax Harmonization Law. The evaluation assesses the policy from the perspective of individual SME taxpayers based on The Four Maxims: equality, certainty, convenience, and economy of collection. The research employs a descriptive qualitative case study evaluation method, focusing on one of the echelon III units in the Directorate General of Taxes (DGT), KPP Pratama Jakarta Setiabudi One. The research methodology uses triangulation, utilizing primary data collection, literature review, and secondary data. Primary data collection involves distributing questionnaires and conducting interviews with individual SME taxpayers and government representatives, including the Fiscal Policy Agency (BKF) and DGT. The research results indicate that the gross turnover   threshold policy meets the principles of fairness and economic benefits. Furthermore, the study shows that there are still individual SME taxpayers who do not report their actual turnover in their annual tax returns. Active involvement from DGT through canvassing methods is needed to improve formal compliance among individual SME taxpayers. Keywords: revenue threshold; The Four Maxims; tax compliance; policy evalution; small medium enterprises (UMKM)